Increasing women's involvement in the workforce can improve dietary diversity - Sangwan, Nikita; Kumar, Shalander (CGIAR GENDER Impact Platform, 2022)
"Key messages - When women are more involved in the workforce, the dietary diversity of their households improves. The extra time that women use at work does not have adverse effects on their health. - Women’s paid and unpaid work impacts dietary diversity in different ways: paid work results in financial independence and empowerment in household decision-making that allows women to diversify diets. Unpaid work increases the number of food groups produced by women for consumption by their households. - Policies and development programs can harness synergies between schemes to improve nutrition and increase women’s employment to pursue global goals of ensuring better food for all."